Comparison on the Physicochemical Parameters of Five Commercially Available Branded Oils in Tansen Bazar - Gautam, Madhab; Bhandari, Varshal (Prāgyik Prabāha, 2023)
Oils are unsaturated triglycerides or lipids which are liquid at room temperature. The physicochemical parameters of oils should be analyzed to assess the quality and functionality of the oil. The parameters like saponification value, acid value, iodine value, and insoluble impurities can identify characteristics of edible vegetable oils available in Nepali market whose characteristics remain indistinct and for this, the quality of individual edible oil also remains unknown. Objective of this research work is to get idea about other applicability of vegetable oils instead of commonly used mustard oils. Five different branded and certified samples of oils: coconut oil, olive oil, castor oil, soybean oil and sunflower oil were collected from different shops of Tansen bazaar for quality analysis. The saponification values, acid values, iodine values and percentage insoluble impurities of the selected oil samples were recorded in the range (178.54-284.70) mg KOH/gm, (0.48-4.48) mg KOH/gm, (8.75-141.2) mg KOH/gm and (0.004-0.078) % respectively. This study showed that all the selected five samples of oils are very good for soap making process or studied coconut oil was observed to produce the best quality soap. Analyzed olive oil was not consumable or good as skin care product either. This study had recommended public not to use pre-heated oil more than one time and also, analyzed sunflower oil had been recommended as the best suitable for all purposes among all samples of oils under study from Tansen.